Engineering a metal–organic framework derived Mn–N4–CxSy atomic interface for highly efficient oxygen reduction reaction. Issue 23 (1st June 2020) - Shang, Huishan; Jiang, Zhuoli; Zhou, Danni; Pei, Jiajing; Wang, Yu; Dong, Juncai; Zheng, Xusheng; Zhang, Jiatao; Chen, Wenxing
Abstract : A sulfur modified Mn–N–C single atom catalyst was constructed through an atomic interface strategy, with outstanding ORR activity in alkaline media. Abstract : Atomic interface engineering is an effective pathway to regulate the performance of single metal atom catalysts for electrochemical reactions in energy applications. Herein, we construct a sulfur modified Mn–N–C single atom catalyst through a metal–organic framework derived atomic interface strategy, which exhibits outstanding ORR activity with a half-wave potential of 0.916 V vs. RHE in alkaline media. Moreover, operando X-ray absorption spectroscopy analysis indicates that the isolated bond-length extending the low-valence Mn–N4 –C x S y moiety serves as an active site during the ORR process. These findings suggest a promising method for the advancement of single atom catalysis.